Analysis on fringing electric field sensor sensitivity based on it geometry shape and sizing: article / Khairul Razman Mohd Razali - Mohd Razali, Khairul Razman (2013)
This project purpose is to analyze the ‘Fringe Electric Field (FEF) Sensor’ sensitivity by varying it geometry shape and electrode size. Fringing electric field (FEF) sensors are commonly used to determine the properties that cannot be directly measure for example electrostatic, temperature, hardness and many others. In this project, the FEF sensor was used to determined the moisture level in soil by measuring its capacitance values. This project will start with simulation using Finite Element Method Magnetic (FEMM) to simulate the FEF sensor. The process then continues with fabricating the FEF sensor using Printed Circuit Board (PCB) technology. The FEF sensor will be tested using LCR meter to measure the capacitance values and the data obtained are varies by the geometry shape, electrode width and number of electrode of the FEF sensor. The data obtained will be tabulated then compare with the simulation data.